2010
DOI: 10.4097/kjae.2010.58.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning may not influence early brain injury induced by focal cerebral ischemia/reperfusion in rats

Abstract: BackgroundExperimental studies have shown that ischemic postconditioning can reduce neuronal injury in the setting of cerebral ischemia, but the mechanisms are not yet clearly elucidated. This study was conducted to determine whether ischemic postconditioning can alter expression of heat shock protein 70 and reduce acute phase neuronal injury in rats subjected to transient focal cerebral ischemia/reperfusion.MethodsFocal cerebral ischemia was induced by intraluminal middle cerebral artery occlusion for 60 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Previous studies demonstrated that the effectiveness of ischaemic PostCon strongly depends on the specific protocol employed. For example, Kim et al (2010) did not note any neuroprotective effect of PostCon elicited by three episodes of 10-s MCA occlusion and 30-s reperfusion after 60-min intraluminal MCA occlusion in rats. In contrast, a robust neuroprotective effect was found after application of six cycles of 30-s ischaemia/30-s reperfusion in the same model (Xing et al 2008).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies demonstrated that the effectiveness of ischaemic PostCon strongly depends on the specific protocol employed. For example, Kim et al (2010) did not note any neuroprotective effect of PostCon elicited by three episodes of 10-s MCA occlusion and 30-s reperfusion after 60-min intraluminal MCA occlusion in rats. In contrast, a robust neuroprotective effect was found after application of six cycles of 30-s ischaemia/30-s reperfusion in the same model (Xing et al 2008).…”
Section: Discussionmentioning
confidence: 79%
“…НСкоторыС Π°Π²Ρ‚ΠΎΡ€Ρ‹ склонны Π²ΠΈΠ΄Π΅Ρ‚ΡŒ Π² процСссС ΠΎΡ‚Ρ‘ΠΊΠ°-набухания ΠΌΠΎΠ·Π³Π° проявлСния СстСствСнного Π·Π°Ρ‰ΠΈΡ‚Π½ΠΎΠ³ΠΎ ΠΌΠ΅Ρ…Π°Π½ΠΈΠ·ΠΌΠ° ΠΈ санации Π½Π΅Ρ€Π²Π½ΠΎΠΉ Ρ‚ΠΊΠ°Π½ΠΈ ΠΏΠΎ Ρ‚ΠΈΠΏΡƒ лимфатичСского Π΄Ρ€Π΅Π½Π°ΠΆΠ° отростками астроцитов. ΠžΡ‚Ρ‘ΠΊ-Π½Π°Π±ΡƒΡ…Π°Π½ΠΈΠ΅ ΠΌΠΎΠ·Π³Π°, ΠΏΠΎ сущСству, являСтся частично ΠΎΠ±Ρ€Π°Ρ‚ΠΈΠΌΠΎΠΉ ΠΏΠ»Π΅ΠΉΠΎΡ‚Ρ€ΠΎΠΏΠ½ΠΎΠΉ Ρ€Π΅Π°ΠΊΡ†ΠΈΠ΅ΠΉ Π½Π° Ρ„ΠΎΠ½Π΅ Π½Π΅Π·Π½Π°Ρ‡ΠΈΡ‚Π΅Π»ΡŒΠ½Ρ‹Ρ… ΠΏΠΎΠ²Ρ€Π΅ΠΆΠ΄Π΅Π½ΠΈΠΉ структур ΠΈ Π½Π΅ΠΎΠ±Ρ€Π°Ρ‚ΠΈΠΌΠΎΠΉ ΠΏΡ€ΠΈ тяТёлых измСнСниях Π½Π΅Ρ€Π²Π½ΠΎΠΉ Ρ‚ΠΊΠ°Π½ΠΈ (Π½Π°ΠΏΡ€ΠΈΠΌΠ΅Ρ€, ΠΏΠΈΠΊΠ½ΠΎΠΌΠΎΡ€Ρ„Π½Ρ‹Π΅ Π³ΠΎΠΌΠΎΠ³Π΅Π½ΠΈΠ·ΠΈΡ€ΠΎΠ²Π°Π½Π½Ρ‹Π΅ Π½Π΅ΠΉΡ€ΠΎΠ½Ρ‹, ΠΊΠ»Π΅Ρ‚ΠΊΠΈ Ρ‚Π΅Π½ΠΈ) [12,16].…”
Section: Comparative Morphometric Characteristics Of Edema-swelling M...unclassified
“…The sections were mounted onto coverslip and photographed with a digital camera. The ischemia size were then analyzed with picture analysis software (Adobe Photoshop CS5) and expressed as a percentage of the pixels of the infarct area relative to the pixels of the whole slice (Kim et al, 2010;Zhao et al, 2003), computed according to the following formula: %Ischemia size = pixels of the infarct area pixels of the whole slice Γ— 100%…”
Section: Ttc Staining and Infarct Measurementmentioning
confidence: 99%